Incidence and clinical characteristics in a Colombian cohort of ocular toxoplasmosis (2008)
Purpose To evaluate the incidence and clinical features of patients with ocular toxoplasmosis in a Colombian cohort. Methods We collected prospectively the clinical features of patients with ocular toxoplasmosis seen at the ‘Universidad del Quindio’ health centre between September 2005 and September 2007 (24 months). Results Seventy patients were included in the analysis (95 affected eyes). The median age at the first episode was 21 years (range: 1–54 years). Thirty-two patients had active lesions (45.7%), one of them had active lesions in both eyes. The acquisition of infection was determined in 14 patients as congenital (20%), in seven as an acquired postnatal infection (10%), and in 49 as undetermined (70%). Bilateral involvement was found in 25 cases (35.7%). Unilateral legal blindness (o20/200) was found in 14 of 37 inactive cases (37.8%). The most frequent complication was strabismus (n: 12; 13.4%). Conclusions There is a high incidence of cases of ocular toxoplasmosis in Quindio region (three new episodes by 100 000 inhabitants by year). Clinical features of ocular toxoplasmosis in Colombia are similar to those reported in other regions but there are no comparative data about the size and number of lesions.